ANALYSIS WORK ENVIRONMENT AND LEADERSHIP ON EMPLOYEE PERFORMANCE (Study at Manado Forestry Service) - Tanor, Gabriella A.L. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
In every company, organization or agency uses a variety of ways and each method in order to continuously improve performance, competitiveness, and quality of work in the company or institution itself. On the other hand, several jobs provide by the government in order to help, continue and develop the government itself to advance Country. The aim of this study is to analyze the effect of work environment and leadership style on employee performance. In this study, population refers to the employees of Manado Forestry Service by using purposive sampling technique and sample size of 63 respondents. This study used associative method through questionnaires and multiple regression analysis. Result and conclusion show that work environment and leadership style significantly influence employee performance. Work environment partial and significant influence on employee performance. Leadership style has partial and significant influence on employee performance. For organizations in this regard Manado Forestry Service, it is advisable to continuously improve the work environment and leadership style, because all of the variables have a significant influence on employee performance. Keywords: work environment, leadership style, employee performance